Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum dan Sesudah Initial Public Offering (IPO) pada Perusahaan yang Listing di BEI - Fitricia, Kevin; Warsitasari, Wahyu Dwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to compare the financial results of IDX companies before and after their IPO to determine if there is a correlation between the two. Purposive sampling was employed to choose a subset of the study population (n=42) from among the full (n=51) population. All information for this study comes directly from the IDX's official website, making it a secondary data source. A company's financial results before and after its initial public offering (IPO) serve as independent and dependent variables, respectively. While a documentation study is utilized to collect data. A comparison of the company's liquidity ratio, leverage ratio, profitability ratio, and activity ratio before and after its IPO was found to be statistically significant (P .05) or not (P >.05), respectively, using the Wilcoxon Signede-rank test method. Keywords: Initial Public Offering (IPO), Liquidity Ratio, Leverage Ratio, Profitability Ratio, and Activity Ratio, Financial Performance.